Social management in the system of providing assistance to victims of domestic violence: the experience of the Paula Panke Women's Center (Paula Panke e. V.) in Berlin (Germany) - Kobylyanska, Vlada (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2025)
The article "Social management in the system of providing assistance to victims of domestic violence: the experience of the Paula Panke Women's Center (Paula Panke e. V.) in Berlin (Germany)" investigates the role and features of management in ensuring the high-quality provision of social assistance to women who have experienced domestic violence.The relevance of the topic is determined by the severity of the problem of violence against women, which requires systemic regulation and the minimization of serious psychological and social consequences.The aim of the article is to define the role of management in ensuring effective assistance to women who have suffered from domestic violence and to analyze management practices using the German center Frauenzentrum Paula Panke e.V. as an example.The author establishes that quality management is a fundamental prerequisite for forming a clear system of procedures, control, and rules that ensures the effectiveness and transparency of a social organization's activities. Management is viewed as a complex set of functions covering the planning, organization, execution, and control of resources, and it consists of managerial, financial, operational, informational, logistical, investment, and other subsystems.A special emphasis is placed on the analysis of external and human resource (HR) management. External management is a critically important link that ensures the informing of target groups, feedback, and the adjustment of programs according to clients' needs. The specifics of the center's HR management include the selection of specialists capable of working in a multicultural environment, as well as systematic prevention of staff emotional burnout.The author concludes that effective management of a women's center must be dynamic, adaptive, and human-centered, aimed at creating a safe environment. The experience of Frauenzentrum Paula Panke e.V. demonstrates that the management system is not just a mechanism for ensuring operations but also a key prerequisite for minimizing harm from violence and the successful social reintegration of women.